Implementation of 21st-Century Skills in General Mathematics and Its Impact on Student Performance: Bases for Developing a Self-Learning Module - Pericano, Christine Impas Catyong; Leonard, Leonard (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
Mathematics plays a crucial role in the 21st century because it emphasises logical and systematic problem-solving processes. This research evaluated the implementation of 21st-century skills in general mathematics instruction and the mathematics performance of the Cebu Technological University San Francisco Campus students for the Academic Year 2022-2023. The study employed a descriptive-correlational research design, utilising researcher-modified questionnaires anchored from the P21 framework, which were pilot-tested, expert-reviewed, and validated. It involved 203 students and perceived a very satisfactory implementation of the 21st-century skills of critical thinking, communication, problem-solving, collaboration, and perseverance in general mathematics instruction. Also, it assessed the students' mathematics performance using a 30-item multiple choice test and found poor performance in all six topics. The study found a weak but statistically significant relationship between the implementation of 21st-century skills and mathematics performance. Among the skills, collaboration showed the strongest positive relationship with mathematics performance, followed by communication, perseverance, and critical thinking. Surprisingly, problem-solving did not demonstrate a significant relationship, suggesting that other factors may also influence performance. The findings emphasise the importance of these skills in improving mathematics performance and provide a foundation for the development of a contextualised self-learning module in general mathematics. Further research is recommended to validate these findings.